Protective effects of medicinal plant-derived metabolites in cardiovascular disease targeting exosomal pathways - Fu, Liwen; Han, Jiaxiu; Lu, Rong; Song, Aifeng; Shen, Ao; Xiong, Changjiang; Liu, Yanzhu; Gao, Zu (Frontiers in Pharmacology, 2025)
Cardiovascular disease (CVD) is a highly prevalent and lethal disease worldwide, and existing conventional therapeutic drugs have limitations due to their side effects. Medicinal plant-derived metabolites have become a research hotspot due to their multi-target and multi-pathway cardioprotective potentials, while exosomal miRNAs, as core regulatory molecules of intercellular communication, play a key role in CVD such as atherosclerosis and myocardial infarction. This paper systematically reviews the mechanisms by which medicinal plant-derived metabolites regulate exosome miRNA or synergize with exosome therapy to protect CVD. For instance, Tanshinone IIA, Astragaloside IV, Paeonol, and Ginsenoside Rg1 can achieve effects such as promoting/inhibiting angiogenesis, anti-inflammation, and vascular remodeling by regulating exosomal miRNA expression. Finally, we look forward to the future direction of Medicinal plant-derived metabolites combined with exosomes in the protection of cardiovascular diseases, and provide a theoretical basis for the application of Medicinal plant-derived metabolites in CVD protection and the development of exosomal miRNA-targeted drugs.